Modeling economic, social and environmental implications of a free trade agreement between the European Union and the Russian Federation - Elena Jarocinska; Maryla Maliszewska; Milan Ščasný (Center for Social and Economic Research (CASE), 2010)
The EU-Russia Partnership and Cooperation Agreement, which entered into force in 1997 foresees the possible establishment of a free trade area (FTA) between the parties. The aim of our study is to evaluate the possible economic, social and environmental impact of such a free trade agreement between the European Union and Russia. The results of the analysis indicate that an EU-Russia FTA will be beneficial to the Russian Federation and the EU27. Some sectors are expected to contract in the medium term, but their importance in total output is small. Over the long run, the majority of sectors in Russia are expected to expand, while only a few sectors in the EU27 are expected to register negligible decreases in output. We estimate that welfare losses from the environmental damages would be very small for Russia (possibly even smaller due to the implementation of greener technologies), and negligible for the EU. Despite some significant negative medium-term social implications in selected sectors in Russia, the overall increase in economic activity and wages, coupled with likely domestic policies aiming at easing the impact of transitional unemployment, are expected to allow for the overall reduction in poverty rates. Overall, the results show that significant welfare gains (2.24% of GDP for Russia) would accrue from the deep FTA scenario involving a significant reduction of NTBs along with additional flanking measures, particularly on competition, IPR protection and corruption, which would help re-branding of Russia as a safe and attractive investment location. Also a number of countries such as Finland, Ireland, Netherlands, Denmark, Estonia, Slovakia, Slovenia and Sweden are expected to see their welfare increase by around 0.5% of GDP.
Keywords: F12; F15; F16; F17; F18; 330; free trade agreement; WTO accession; European Union; Russian Federation; labor market; environment; NTBs; CGE; Freihandelszone; Regionale Wirtschaftsintegration; WTO-Mitgliedschaft; Internationale Wirtschaftsbeziehungen; Arbeitsmarkt; Umwelt; EU-Staaten; Russland